A Study of Customer Satisfaction in Private and Public Sector Banks - Taxak, Ramesh H; Kaur, Manjeet (Gyan Management Journal, 2009)
In the past, banking was concerned only with borrowings and lending activities. But at present banking is catering entire requirement of individual a,stomer and is emerging as potential sector for the consistent growth of business. Customer retention is of the top priority of the banks. The main aim of this research paper is to assess and re-assess how customers perceive bank services, what are the emerging customer expectations and t.o study customer satisfactio11 level with banking services provided by the Public and Private sector Banks. A sample of 200 respondents had been drawn from the various socio-economic strata, at different designation and having different educatio1.al qualification and belongs to different age group on the line of "Convenience Sampling" method. On the basis of foregoing analysis, was concluded that Public sector Banks provides better services to their customers than Private sector Banks. The customers of Public sector Banks are more satisfied with traditional hanking services and Bank Accounts as compared to Private sector Banks. Whereas customers of Private sector Banks are more satisfied with Counter Services provided by the bank.